2022
DOI: 10.1155/2022/1375864
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotection of Paederia scandens (Lour.) Merr. on Acetaminophen-Related Hepatic Injury Rats by 1H-NMR-Based Metabonomics Coupled with Network Pharmacology

Abstract: Background. Acetaminophen-related hepatic injury (ARHI) is a kind of acute hepatic injury caused by overdosing acetaminophen, which is mainly related to toxic metabolite production, oxidative stress, and mitochondrial dysfunction. The extract of Paederia scandens (Lour.) Merr. (PSM) has the abilities of anti-inflammatory, antivirus, and antioxidation. Research studies showed that PSM could improve acute or chronic hepatic injury, while the mechanism of which is still indistinct. Methods. Here, the authors appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In the current study, the elevated AST and ALT levels indicated that the liver had been damaged in the NAFLD rats, which further confirmed that a NAFLD model with liver injury was established in the rats. Surprisingly, we found that dietary Paederia scandens significantly reduced AST and ALT levels in NAFLD rats, suggesting an ameliorative effect of Paederia scandens on liver damage, which was consistent with the results of previous studies (Peng et al 2015;Tang et al 2022). Numerous studies have reported that the hepatoprotective activity of linalool alleviates liver injury by regulating the 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the elevated AST and ALT levels indicated that the liver had been damaged in the NAFLD rats, which further confirmed that a NAFLD model with liver injury was established in the rats. Surprisingly, we found that dietary Paederia scandens significantly reduced AST and ALT levels in NAFLD rats, suggesting an ameliorative effect of Paederia scandens on liver damage, which was consistent with the results of previous studies (Peng et al 2015;Tang et al 2022). Numerous studies have reported that the hepatoprotective activity of linalool alleviates liver injury by regulating the 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the antiinflammatory and hepatoprotective effects of Paederia scandens were observed in rats, comprising attenuated liver damage and reduced alanine aminotransferase (ALT) and aspartate transaminase (AST) levels (Peng et al 2015). Furthermore, network pharmacology analyses were conducted to investigate the anti-inflammatory and hepatoprotective mechanisms of Paederia scandens, which indicated that it inhibited the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) and inducible nitrous oxide synthase (iNOS)/nuclear factor kappa B (NF-κB) signaling pathways to exerts antiinflammatory effects (Chen et al 2022;Tang et al 2022).…”
mentioning
confidence: 99%
“…Asperuloside, for instance, has been shown to mitigate inflammation by inhibiting the expression of pro-inflammatory cytokines and modulating immune responses [5] . Scandoside exhibits similar effects and has also been noted for its potential antioxidant properties [6] . The presence of these iridoids not only supports the traditional use of the plant in treating pain and inflammation but also opens avenues for new therapeutic uses.…”
Section: Iridoidsmentioning
confidence: 75%